Analysis of Child Marriage Prevention in Sidoarjo Regency - Sukmana, Hendra; Suhartini, Dian (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2019)
Writer 's it aims to analyze and describe the strategies an obstacle Strategies Prevention of Marriage Children in the District of Sidoarjo . Writer 's is based on a fact that child marriages still occur in age or mentality of the child's thought patterns that are caused due to the circumstances pregnant at the outside of marriage on children that are into a problem which should be in preventing the marriage of children . Methods The author 's is using descriptive qualitative , techniques of collecting the data is done with interviews in depth , observation and study of literature that is relevant . The technique of determining the informants used purposive sampling. The informant in the Writer 's this is the Head of the Protection of Women's Rights and Protection , Head of Fulfillment Rights of the Child , Head of Security Family & Community Engagement , Head of Processing Data Population at the Department P3AKB, Ket ua Children's Forum and Actors Marriage Children in the District of Sidoarjo . Mechanical analysis of the author 's of this is the type of analysis of qualitative Referring to the theory of Miles and Huberman. The author 's results show that , prevention of child marriage is successful , as evidenced by the programs that run on the prevention of child marriage so that the number of child marriages in Sidoarjo can be reduced, in the absence of a culture of "marrying children as soon as possible so they don't become old virgins" This also supports the decline in the number of child marriages. K endala in the prevention of marriages child one of them is the lack of willingness of young people to think critically the mindset of young people should continue learning with the strategy of prevention marriage of children who applied P3AKB , associated with P ola think those parents who do not give priority to the ideals of children then from the Office of P3AKB should provide regular counseling to parents as one of the strategies of prevention marriage of children , so the mindset of parents are not primitive. Regarding the use of technology, parents must limit the use of cellphones, laptops, computers and so on